Nathaniel Willy, Scared Silly. - Mathews, Judith; Robinson, Fay; Natchev, Alexi (Illustrator) (New York : Bradbury Press, 1994)
Nathaniel Willy is scared silly by a squeak in his door, so Gramma must put the farm animals in bed with him for company.
K-3
Keywords: Folklore - United States; Stories in rhyme; Robinson, Fay